PENGEMBANGAN MANAJEMEN RANTAI PASOK KOPI ARABIKA KINTAMANI BALI - Siswandi, Try Ono; Suryawan Wiranatha, A.A.P.Agung; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
The purpose of this study were to determine the condition of Kintamani Arabica coffee supply chain management which included the structures, mechanisms and institutional supply chain, and to determine the priority of the recomendations of the development in order to improve the performance management of the supply chain of Arabica Coffee Kintamani. The research was carried out at the Catur Village in Kintamani Subdistrict, Bangli Regency, up to the distribution channel to Denpasa r. The instrument used to collect supply chain performance data were questionnaire s . The format of the questionnaire followed to the terms and conditions required by AHP. The distribution pattern of Kintamani Arabica coffee is : Pattern 1 : Farmers à UPH à Coffee shop à End consumers. Pattern 2: Farmers à Cooperation à End consumers. Pattern 3: Farmers à Collectors à PT. Mengani à Retailer s à End consumers. The results of the analysis with the AHP method indicate d that the criteria of increasing access to market, alternative management costs, and production cost performance indicators were the priority that plays a role in the development of a competitive supply chain management system for Kintamani Arabica coffee. Keywords : AHP Method, Supply Chain, Arabica Coffee